Architecture and functioning of child and adolescent mental health services: a 28-country survey in Europe. (September 2017) - Signorini, Giulia; Singh, Swaran P; Boricevic-Marsanic, Vlatka; Dieleman, Gwen; Dodig-Ćurković, Katarina; Franic, Tomislav; Gerritsen, Suzanne E; Griffin, James; Maras, Athanasios; McNicholas, Fiona; O'Hara, Lesley; Purper-Ouakil, Diane; et al.
Summary: The WHO Child and Adolescent Mental Health Atlas, published in 2005, reported that child and adolescent mental health services (CAMHS) in Europe differed substantially in their architecture and functioning. We assessed the characteristics of national CAMHS across the European Union (EU), including legal aspects of adolescent care. Using an online mapping survey aimed at expert(s) in each country, we obtained data for all 28 countries in the EU. The characteristics and activities of CAMHS (ie, availability of services, inpatient beds, and clinicians and organisations, and delivery of specific CAMHS services and treatments) varied considerably between countries, as did funding sources and user access. Neurodevelopmental disorders were the most frequent diagnostic group (up to 81%) for people seen at CAMHS (data available from only 13 [46%] countries). 20 (70%) countries reported having an official national child and adolescent mental health policy, covering young people until their official age of transition to adulthood. The heterogeneity in resource allocation did not seem to match epidemiological burden. Substantial improvements in the planning, monitoring, and delivery of mental health services for children and adolescents are needed.